Analysis of Students' Visuospatial Reasoning Reviewed Based on Mathematics - Cut Latifah Zahari; Nazhatul Sahima; Cindy Cyntia Devi (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
Visuospatial mathematical reasoning is an essential skill that needs to be developed due to its positive impact on various aspects of life, particularly in addressing challenges and solving problems effectively. For prospective teachers, this ability is crucial in helping students overcome learning difficulties in the classroom. This study aims to analyze the profile of visuospatial reasoning skills among prospective mathematics teachers based on their cognitive styles. Using a qualitative approach, the study involved 30 prospective mathematics teacher students in the 2023/2024 academic year. Data were collected through a visuospatial reasoning test, cognitive style questionnaire, interviews, and documentation, and were analyzed descriptively using triangulation methods. The expected outcomes include a reference book and a Scopus-indexed scientific article. This research also supports the strategic research plan of Universitas Muslim Nusantara Al Washliyah for 2022–2026 in the field of mathematical ability studies and aligns with the university’s humanist, independent, and Islamic vision.